A case report of pregabalin misuse leading to drug dependence - Luo, Yaan; Zhou, Xiafeng; Xiang, Ao; Zeng, Yaqi; Luo, Jing; Zhou, Bojie; Guo, Nana; Zhou, Xuhui (Frontiers in Psychiatry, 2025)
Pregabalin misuse and dependence have become emerging concerns in recent years, particularly in regions where traditional drug-related crimes have been curbed, prompting users to seek alternative substances. Although pregabalin is primarily used for treating conditions such as epilepsy, neuropathic pain, and generalized anxiety disorder, its sedative and euphoric effects make it prone to misuse. This case report presents a 20-year-old male who developed pregabalin dependence after using the drug intermittently at escalating doses over a year. He experienced withdrawal symptoms including palpitations, tremors, irritability, insomnia, and auditory hallucinations upon cessation of the drug, which were alleviated by resuming pregabalin use. Upon admission, he was diagnosed with pregabalin dependence, hyperuricemia, and thyroid nodules. The patient underwent a comprehensive treatment plan involving benzodiazepines, antidepressants, and antipsychotics, leading to substantial improvement in mood, anxiety, psychotic symptoms, and withdrawal symptoms. This case highlights the growing issue of pregabalin misuse, the associated withdrawal symptoms, and the importance of early intervention and systematic treatment strategies. It emphasizes the need for stricter prescription controls, patient education on the risks of misuse, and multidisciplinary approaches to the treatment of pregabalin dependence. Further research is necessary to better understand the mechanisms behind pregabalin misuse and to develop improved prevention and treatment protocols.